Pere Ballart, Jordi Malé, Marcel Ortín, Joaquim Espinós & Gonçal López-Pampló, «Joan Fuster i la ironia», València, PUV, 2017, 162 pp. - Ferrando, Mireia (Caplletra. Revista Internacional de Filologia, 2018)
Ressenya sobre el llibre de Pere Ballart, Jordi Malé, Marcel Ortín, Joaquim Espinós & Gonçal López-Pampló, «Joan Fuster i la ironia», València, Publicacions de la Universitat de València, 2017, 162 pp., ISBN: 978-84-9134-008-9.